KONSEP KOTA DALAM SINERGI AL-QUR’AN - Kusumadewi, Tarranita (ULUL ALBAB Jurnal Studi Islam, 2008)
The city is one of important aspects of the earth. The universe has been created with various kinds of creature. However, to be able to survive, there are two important things to do: a) surviving to compete, and b) surviving to live. The human being becomes the subject for any building plans for nation advancement. On the other side, the environ- ment which becomes the object of building plans is frequently ignored. It should not happen as al-Qur'an states that the universe is created for human's benefits based on its Standard and function. When the universe does not function as its standard, there will be a disaster. For that reason, building infrastructure in the city should consider the surroundings, and does not make the nature as the place of throwing away. The building process which synergies with al-Qur'an aims to make people aware and change their behavior for the safety of the universe. In al-Qur'an, it is stated that if the human is not back to his/her 'fitrah' will disappear because of any damages created by human himself.